RESILIENSI PADA ANAK DENGAN KANKER - Irma Rosalinda; Herdiyan Maulana; Nur Fitriah (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The aim of this research was to describe the resilience in the children with cancer. Resilience was obtained through identification of three resilience factors: â€œI Amâ€ for the individual strength in personal, â€œI Haveâ€ for external support and the sources, and â€œI Canâ€ for interpersonal skills, and output from interaction of the three factors consisting of trust, autonomy, initiative, industry, and identity. The research took places in some locations of cancer rehabilitation: Cancer Foundation (YKAKI) and the hospital. Using qualitative approach, this research was completed in three months (April â€“ June 2012). The subjectâ€™s resilience description was obtained by interviewing the children with cancer, relatives (mother and uncle), instructor, and doctor who handled the children with cancer. The results of this research are both of the subjects can develop resilience characteristic well. However, there are some differences between the two subjects. The1st subject achieves resilience attitude more depth on interaction â€œI Haveâ€ and â€œI Canâ€ factors clearly though , is still supported by â€œI Amâ€ factor. Whereas the 2nd subject achieves resilience attitude more on â€œI Amâ€ and â€œI Canâ€ factors though â€œI Haveâ€ factor is still fulfilled. Moreover,the 1st subject is able to establish initiative and industry better than the 2nd subject.